PLS3 Overexpression Delays Ataxia in Chp1 Mutant Mice - Janzen, Eva; Wolff, Lisa; Mendoza-Ferreira, Natalia; Hupperich, Kristina; Delle Vedove, Andrea; Hosseinibarkooie, Seyyedmohsen; Kye, Min Jeong; Wirth, Brunhilde (Frontiers in Neuroscience, 2019)
Many neurodegenerative disorders share common pathogenic pathways such as endocytic defects, Ca2+ misregulation and defects in actin dynamics. Factors acting on these shared pathways are highly interesting as a therapeutic target. Plastin 3 (PLS3), a proven protective modifier of spinal muscular atrophy across species, is a remarkable example of the former, and thereby offers high potential as a cross-disease modifier. Importantly, PLS3 has been linked to numerous proteins associated with various neurodegenerative diseases. Among them, PLS3 directly interacts with calcineurin like EF-hand protein 1 (CHP1), whose loss-of-function results in ataxia. In this study, we aimed to determine whether PLS3 is a cross-disease modifier for ataxia caused by Chp1 mutation in mice. For this purpose, we generated Chp1 mutant mice, named vacillator mice, overexpressing a PLS3 transgene. Here we show that PLS3 overexpression (OE) delays the ataxic phenotype of the vacillator mice at an early but PLS3 overexpression delays ataxia in Chp1 mutant mice not later disease stage. Furthermore, we demonstrated that PLS3 OE ameliorates axon hypertrophy and axonal swellings in Purkinje neurons thereby slowing down neurodegeneration. Mechanistically, we found that PLS3 OE in the cerebellum increases membrane targeting and/or expression of Na+/H+ exchanger (NHE1), an important CHP1 binding partner and a causative gene for ataxia, when mutated in humans and mice. This data supports the hypothesis that PLS3 is a cross-disease genetic modifier for CHP1-causing ataxia and spinal muscular atrophy.